Review of 'The Changing Face of Christianity: Africa, the West, and the World.' - Kefas Lamak (African Theological Journal for Church and Society)
Lamin Sanneh and Joel A. Carpenter (eds.), Oxford University Press, Oxford: 2005, ISBN 9780195177275, 238 pp.